Understanding the under 3s and the implications for education - Rayna, Sylvie; Laevers, Ferre (London : Routledge, 2014)
This text originated from an awareness of the persistent lack of knowledge supporting a more respectful reception and approach to the youngest in our changing societies. It follows initiatives of networks of researchers from several countries, sharing insights from current studies carried out in their different cultures. Introduced by a state of art review-like chapter on birth to 3 literature, the book, which can be pictured as a composition, begins with a journey inside the creativity of these young persons and a picture of a companionable learning.
Introduction: Understanding children from 0 to 3 years of age and its implications for education. What's new on the babies' side? Origins and evolutions / Sylvie Rayna and Ferre Laevers -- What young children give to their learning, making education work to sustain a community and its culture / Colwyn Trevarthen -- Companionable learning: a mechanism for holistic well-being development from birth / Rosemary Roberts -- Sharing attention and activities among toddlers: the spatial dimension of the setting and the educator's role / Tullia Musatti and Susanna Mayer -- Early education for diversity: starting from birth / Jia Oliveira-Formosinho and Sara Barros Araujo -- Look at me! Does the adult truly see and respond to the child in Finnish day-care centres? / Marjatta Kalliala -- From the curriculum framework to its dissemination: the accompaniment of educational practices in care facilities for children under three years / Florence Pirard -- Promoting language in under 3s. Assessing language development and the quality of adult intervention / Ferre Laevers, Evelien Buyse, Annemieke Willekens and Tine Janssen.
Includes bibliographical references and index.
Keywords: Education, Preschool; Preschool children; Child development; Preschool teaching